The central role of the chemokine receptor, CXCR4, in haemopoietic stem cell transplantation: will CXCR4 antagonists contribute to the treatment of blood disorders? - Watt, S; Forde, S (2008)
Recent clinical trials have used CXCR4 antagonists for the rapid mobilization of CD34(+) haemopoietic stem/progenitor cells (HSC/HPC) from the bone marrow to the blood in patients refractory to granulocyte-colony-stimulating factor (G-CSF). These antagonists not only mobilize non-cycling cells with a higher proportion of repopulating cells, but also enhance CD34(+) cell mobilization when used in combination with G-CSF. Here, we review the importance of CXCR4 and its ligand CXCL12 in haemopoiesis, and the potential roles of CXCR4 antagonists in the clinical HSC transplant setting.